Needleless acupuncture using low-level laser therapy - Amandeep Chopra; Amarpreet Kaur; Mallika Sethi; Farheen Khan; Prerna Mohan; Nikhil Sharma (Wolters Kluwer Medknow Publications, 2019)
Introduction: Acupressure works to stimulate (tonify or sedate) specific reflex points located along the lines of energy. In needleless or laser acupuncture, low-intensity lasers are used to stimulate the trigger points, thereby curing many medical conditions. The use of this is called low-level laser therapy (LLLT). The aim of this article is to give a brief overview on needleless acupuncture using LLLT. Methodology: A literature search using keywords such as "laser acupuncture," "needleless acupuncture," and "low-level laser therapy" was made on Google Scholar, PubMed, PubMed Central, Science Direct, and Scopus. Results: Needleless acupuncture or laser acupuncture is one of the most popular methods for treating pain in the world. It has proved to be an effective option for various existing treatments and as a supplement to many current treatments as well. Conclusion: Acupressure with lasers is a proven, natural, and cost-effective professional and self-care system of treatment that can improve the quality life of patients.